2001
DOI: 10.1055/s-2001-919033
|View full text |Cite
|
Sign up to set email alerts
|

Role of Molecular Adsorbent Recycling System (MARS) in the treatment of patients with acute exacerbation of chronic liver failure

Abstract: SUPPLEMENT nnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnn nWe demonstrated a 65.5 % overall survival rate in eight consecutive patients suffering from acute exacerbation of chronic liver disease following treatment with the MARS detoxication system. This study joins other reports concerning the utility of the MARS system in supporting patients with liver failure. In contrast to the regular methods of hemodiafiltration, this system was designed to remove both low and middle molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 0 publications
3
45
3
1
Order By: Relevance
“…In the light of this fact, it is interesting that hemodynamic studies have indicated that the MARS system exerts a beneficial influence on CO, SV, SVRI [20][21][22][23] and MAP [20][21][22][23][24][25][26] . The present study cannot demonstrate such beneficial changes, neither in the Prometheus nor in the hemodialysis group; however, there was a significant increase in MAP in the MARS group.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of this fact, it is interesting that hemodynamic studies have indicated that the MARS system exerts a beneficial influence on CO, SV, SVRI [20][21][22][23] and MAP [20][21][22][23][24][25][26] . The present study cannot demonstrate such beneficial changes, neither in the Prometheus nor in the hemodialysis group; however, there was a significant increase in MAP in the MARS group.…”
Section: Discussionmentioning
confidence: 99%
“…MARS does not alter blood cell counts and arterial blood gases and does not generate haemodynamic instability 6. Improvement in mean arterial pressure (MAP), systemic vascular resistance, cardiac output and cerebral blood flow (due to reduced cerebral oedema) have repeatedly been demonstrated 17 31 32 37 38. Improvement in HE grade during MARS treatment has frequently been observed regardless of the aetiology of the liver failure 6 17 21 31 38 39 40 41 42 43.…”
Section: Liver Support For Patients With Liver Failure: State Of the Artmentioning
confidence: 99%
“…Although several investigators23 34 35 have described the potential beneficial effects of MARS as a treatment of type 1 HRS,22 others have not reported MARS having any effects on renal function,24 especially in patients with advanced cirrhosis.…”
Section: Discussionmentioning
confidence: 99%